Xavier Kalck, Pluralism, Poetry, and Literacy: A Test of Reading and Interpretive Techniques - Malkin, R (Association française d'Etudes Américaines, 2023)
Xavier Kalck, Pluralism, Poetry, and Literacy: A Test of Reading and Interpretive Techniques, New York, Routledge, 2021, 198 p., ISBN : 9780429200786 (e-book), £31.19.